Enabling Adaptive Mesh Refinement for Spectral-Element Simulations of Turbulence Around Wing Sections - Tanarro, Alvaro; Mallor, Fermin; Offermans, Nicolas; Peplinski, Adam; Vinuesa, Ricardo; Schlatter, Philipp (Flow Turbulence and Combustion, 2020)
The implementation of adaptive mesh refinement (AMR) in the spectral-element method code Nek5000 is used for the first time on the well-resolved large-eddy simulation of the turbulent flow over wings. In particular, the flow over a NACA4412 profile with a 5 ∘ angle of attack at chord-based Reynolds number Re c= 200 , 000 is analyzed in the present work and compared with a previous conformal simulation used as baseline. The mesh, starting from a coarse resolution, is progressively and automatically refined by means of AMR, which allows for high resolution near the wall and wake whereas significantly larger elements are used in the far-field. The resulting mesh, which remains unchanged in the production runs (i.e. AMR is used to create the final mesh, which is then fixed), is of higher resolution than those in previous conformal cases, and it allows for the use of larger computational domains, avoiding the use of precursor RANS simulations to determine the boundary conditions. This is achieved with, approximately, 2 times lower total number of grid points if the same spanwise length is used. Turbulence statistics obtained in the AMR simulation show good agreement with the ones obtained with the conformal mesh, and the pressure-coefficient distribution along the wing surface matches pressure-scan experimental data obtained in the MTL wind tunnel at KTH. The use of AMR is therefore expected to enable the simulation of high-Reynolds numbers turbulent flows over complex geometries (such as wings), thus allowing the study of pressure-gradient effects at high Reynolds numbers relevant for practical applications.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adaptive mesh refinement; Adverse pressure gradient; Airfoil; Large-eddy simulation; Turbulent boundary layer